2016
DOI: 10.1111/eci.12588
|View full text |Cite
|
Sign up to set email alerts
|

Intact FGF23 and α‐klotho during acute inflammation/sepsis in CKD patients

Abstract: Acute inflammation/sepsis suppresses the active form of FGF23 and activates α-Klotho, the latter effect being likely attributable to enhance proteolysis of FGF23 molecule. iFGF23 downregulation and α-Klotho upregulation during acute sepsis may participate into the counter-regulatory response to severe inflammation in CKD patients with sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The DII has been previously validated with several inflammatory markers such as C-reactive protein, interleukin-6, and homocysteine [28][29][30]. Previous studies have suggested that a high DII, which represents a pro-inflammatory diet, may increase the incidence of age-related chronic diseases and all-cause mortality [7,31]. However, to the best of our knowledge, there are no previous studies investigating the association between DII and well-recognized anti-ageing biomarkers such as the S-Klotho protein.…”
Section: Discussionmentioning
confidence: 99%
“…The DII has been previously validated with several inflammatory markers such as C-reactive protein, interleukin-6, and homocysteine [28][29][30]. Previous studies have suggested that a high DII, which represents a pro-inflammatory diet, may increase the incidence of age-related chronic diseases and all-cause mortality [7,31]. However, to the best of our knowledge, there are no previous studies investigating the association between DII and well-recognized anti-ageing biomarkers such as the S-Klotho protein.…”
Section: Discussionmentioning
confidence: 99%
“…These hyperoxaluric rats may have enhanced gene activity, as previously reported in CDDP-induced kidney injury, although it was decreased in the volume depletion model [ 25 ]. In the sepsis model, acute inflammation suppressed FGF23 expression, which in turn upregulated Klotho synthesis [ 9 ]. It is plausible that the elevated Klotho mRNA expression was caused by a lack of negative feedback due to reduced FGF23 or Klotho protein production, and the failure in mRNA translation, such as endoplasmic reticulum (ER) stress induced by ROS and inflammation, inhibited Klotho protein production.…”
Section: Discussionmentioning
confidence: 99%
“…Associations between inflammatory markers and FGF23 have been reported in many inflammatory diseases (•56-62). Recently, we and others have shown that inflammatory cytokines are direct regulators of FGF23 production in cardiac fibroblasts (63) and osteoblasts (•24, •25).…”
Section: Inflammation Regulates Fgf23 Production and Cleavagementioning
confidence: 97%